2020
DOI: 10.1007/s10068-019-00730-5
|View full text |Cite
|
Sign up to set email alerts
|

Pine needle hexane extract promote cell cycle arrest and premature senescence via p27KIP1 upregulation gastric cancer cells

Abstract: Pinus densiflora sieb. et zucc.(pine needle) is a traditional medicine used in several East Asian countries. However, the efficacy of pine needle has rarely been reported. In this study showed that the anti-proliferative effects and the mechanisms of hexane layer of pine needle MeOH extract (PNH) on gastric cancer cells. At first, PNH inhibited the proliferation of gastric cancer cells in a dosedependent manner. Moreover, PNH treatment induced G1 phase cell cycle arrest through the increased p27 KIP1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Needles, pollen, cones, and cortices derived from pine trees have been used as antibacterial, anti-inflammatory, and preservative agents in traditional medicine ( 29 ). Particularly, pine needles are crude drugs that are effective for preventing diseases such as rheumatism, gastroenteric trouble, and asthma ( 30 , 31 ). PN5, which consists of 11 amino acids, was isolated from pine needles and showed antibacterial activity against foodborne bacteria in a previous study ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Needles, pollen, cones, and cortices derived from pine trees have been used as antibacterial, anti-inflammatory, and preservative agents in traditional medicine ( 29 ). Particularly, pine needles are crude drugs that are effective for preventing diseases such as rheumatism, gastroenteric trouble, and asthma ( 30 , 31 ). PN5, which consists of 11 amino acids, was isolated from pine needles and showed antibacterial activity against foodborne bacteria in a previous study ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pine bark extracts are effective scavengers of free radicals and reactive oxygen species, can lower lipid levels in blood serum and may help to prevent disease and delay aging ( Schafer et al, 2006 ; McGrath et al, 2015 ). PNs of form P. densiflora were used for folk medicine and for various disease prevention such as rheumatitis, hemorrhage, gastroenteric trouble, hypertension, and asthma ( Kwak et al, 2006 ; Kim et al, 2020b ). Recent scientific researches have shown that PNs form P. densiflora have antimicrobial, anti-viral, antioxidant, anti-mutagenic, anti-thrombosis, anti-asthmatic, and anti-inflammatory, and anti-cancer effects ( Kwak et al, 2006 ; Park and Lee, 2011 ; Park et al, 2016 ; Ahn et al, 2018 ; Mostafa et al, 2018 ; Ha et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%